A Multicenter Randomized Three‐Arm Phase II Study of (1) Everolimus, (2) Estrogen Deprivation Therapy (EDT) with Leuprolide + Letrozole, and (3) Everolimus + EDT in Patients with Unresectable Fibrolamellar Carcinoma. (26th May 2020) - El Dika, Imane; Mayer, Robert J.; Venook, Alan P.; Capanu, Marinela; LaQuaglia, Michael P.; Kobos, Rachel; O'Neill, Allison F.; Chou, Joanne F.; Ly, Michele; Ang, Celina; O'Reilly, Eileen M.; Gordan, John D.; et al.
Abstract: Trial Information: ClinicalTrials.gov Identifier: https://clinicaltrials.gov/ct2/show/NCT01642186NCT01642186 Sponsor: Memorial Sloan Kettering Cancer Center Principal Investigator: Ghassan K. Abou‐Alfa IRB Approved: Yes Click here to access other published clinical trials . Lessons Learned : FLC is a complex cancer with many implicated oncogenic pathways. Single or dual targeting does not appear to alter the natural history of the cancer, and novel therapeutics are needed. Estrogen deprivation therapy with letrozole and leuprolide, alone or in combination with the mTOR inhibitor, everolimus, did not demonstrate clinical activity in advanced fibrolamellar carcinoma. The study drugs were well tolerated when administered as single agents or in combination in this patient population. This study demonstrates that, despite the rarity of FLC, multicenter therapeutic clinical trials are feasible and support the value of this consortium. Background: Fibrolamellar carcinoma (FLC) is an uncommon malignancy in young people and is sometimes associated with pregnancy and oral contraceptive use. Immunohistochemical staining and genetic profiling of FLC tumor specimens have revealed aromatase overexpression. The overexpression of mTOR and S6 kinase has been noted in 25% of FLC. On the basis of interaction between estrogen and the PI3K/Akt/mTOR pathway, we hypothesized that suppression of estrogen and mTOR signaling could have antineoplastic activity in FLC. Methods: Patients were randomized to arm A (everolimus), arm B (letrozole/leuprolide; estrogen deprivation therapy [EDT]), or arm C (everolimus/letrozole/leuprolide). Upon disease progression, patients in arm A or B could proceed to part 2 (everolimus/letrozole/leuprolide). The primary endpoint was progression‐free survival (PFS) at 6 months (PFS6) assessed using a Simon's minimax two‐stage design, hypothesizing an improvement in PFS6 from 40% to 64% with the study regimen. Results: Twenty‐eight patients were enrolled. An unplanned analysis was performed because of perceived concern for lack of efficacy. Stable disease was observed in 9 of 26 evaluable patients (35%). PFS6 was 0%. Median overall survival (OS) was 12.4 months (95% confidence interval [CI], 7.4–20.9) for the whole study cohort. Grade 3 adverse events in ≥10% of patients were nausea (11%), vomiting (11%), anemia (11%), elevated aspartate transaminase (AST; 32%), alanine transaminase (ALT; 36%), and alkaline phosphatase (14%). All 28 patients experienced an event for PFS outcome, and four deaths were due to disease progression. Conclusion: Neither EDT nor mTOR inhibition improved outcomes in FLC. Other treatment strategies are needed.